Supporting factors and coping mechanisms for quality of life: Housewives and career women's perspective - Priyantini, Diah (Universitas Airlangga, 2023)
Introduction: The quality of life between housewives and career women facing chronic hepatitis B shows differences in coping abilities, and is influenced by several causal factors. This study aimed to explore the quality of life of housewives and career women experiencing chronic hepatitis B.Methods: This qualitative phenomenological study consisted of 14 women (seven housewives and seven career women) with chronic hepatitis B. The instruments used to collect information from participants were in-depth interviews about the supporting factors and coping mechanisms that influenced their quality of life. Participants were recruited using purposive sampling, and data were analyzed using the Colaizzi technique to describe the theme.Results: The results showed two major themes from the participants' answers: supporting factors and coping mechanisms. The sub-themes of partner support, family support, peer group support, and social community support made up the supporting factors. Meanwhile, coping mechanisms consisted of adaptive coping, improving knowledge, interacting with other people, problem-solving, and changing lifestyles and controlled routines. On the other hand, maladaptive coping caused participants to isolate, think negatively, grieve excessively, and show stress or depression symptoms.Conclusions: Housewives with chronic hepatitis B have a better quality of life than career women because they are more accepting and have better-coping mechanisms in facing this condition. The research study results can be implicated in nursing interventions to improve the coping abilities of women with chronic Hepatitis B. Keywords: chronic hepatitis B; coping mechanism; quality of life; supporting factors; women